Idea kształcenia akademickiego w dobie AI. Wprowadzenie do zagadnienia – rozmowa z ChatGPT - Barańska , Magdalena (Studia Edukacyjne, 2024)
The purpose of this article is to introduce the subject of the entry of artificial intelligence into every-day life and educational practice at the level of academic education. ChatGPT has become a world-wide phenomenon. It is used by everyone, laymen and professionals alike, including university students and staff. Artificial intelligence prompts, checks, and inspires. It can write credit papers and short essays for students and explain issues and concepts. For lecturers and researchers, it can be a significant aid and can accelerate their work. ChatGPT can generate texts of any complexity and subject matter, compose essays and reports, write a funny story, or suggest ideas for new projects. It can edit a summary for a 5-year-old, an explanation for a senior citizen, synthetic arguments or counterarguments for a subject matter expert, or trivia for an academic teacher. While it has a positive impact on the educational process, it also poses potential threats and will undoubtedly change the education environment. Studying and academic work at a university will never again be like it was before 2023. This article addresses the changes that may take place at universities due to artificial intelligence in the form of ChatGPT. The author is aware that because of the dynamic advances in the field of LLMs, the written text is only up-to-date at the time of writing. Furthermore, the study includes ChatGPT’s responses on the role it can, in its view, play in the academic learning process.